Expression and Possible Role of Silent Mating Type Information Regulation 2 Homolog 1 in Post-necrotizing Enterocolitis Stricture in vivo and in vitro - Chen, Rui; Lv, Chengjie; Zhao, Yun; Gu, Weizhong; Zhang, Luyin; Shi, Bo; Tou, Jingfa (Frontiers in Pediatrics, 2022)
Purpose: To investigate the expression and possible role of SIRT1 in post-necrotizing enterocolitis stricture. Methods: The expression characteristics of SIRT1 and TGF-β1 in post-necrotizing enterocolitis stricture were detected by immunohistochemistry. The siRNA-SIRT1 was used to inhibit the expression of SIRT1 in IEC-6 cells, and qRT-PCR, WB and ELISA were utilized to detect the changes of TGF-β1, NF-κB, TNF-α, ZO-1 and VEGF expression. The IEC-6 cell proliferation and migration ability were tested via CCK8 kit and Transwell test. The expression of E-cadherin and Vimentin in cells was detected by immunofluorescence. Results: The CRP ， IL-6，IL-10 and IFN-γ in the serum of NEC intestinal stenosis patients were significantly higher than the reference values. The SIRT1 protein was under-expressed and the TGF-β1 protein was overexpressed in NEC intestinal stenosis tissue. And the expression of SIRT1 was negatively correlated with TGF-β1. At the time of diagnosis of NEC, the expression of SIRT1 decreased when those children with respiratory distress syndrome and CRP increased. After inhibiting the expression of SIRT1 in IEC6 cells, the expression levels of TGF-β1, Smad3, and NF-κB were decreased, and the expression of ZO-1 was decreased. The proliferation and migration ability of IEC6 cells were decreased significantly, and the expression of E-cadherin and Vimentin proteins in IEC6 cells did not change significantly. Conclusion: Promotion of intestinal fibrosis by inflammation may be the mechanism of post-necrotizing enterocolitis stricture. SIRT1 may be a protective protein of NEC. The probable mechanism is that SIRT1 can regulate intestinal fibrosis and can protect the intestinal mucosal barrier function to participate in the process of post-necrotizing enterocolitis stricture.